Risk of WMSDs in monofunctional and multifunctional workers in a Brazilian footwear company - Wilza Karla dos Santos Leite; Luiz Bueno da Silva; Erivaldo Lopes de Souza; José Guilherme Barbosa Fernandes; Geraldo Alves Colaço (Production)
Abstract This study aimed to analyze the risk of musculoskeletal disorders in monofunctional and multifunctional workers in a footwear company. The sample comprised 114 workers in the shoe production sector. The method Occupational Repetitive Actions was used to assess the risk of work-related musculoskeletal disorders (WMSDs). Proportional odds models were constructed, relating the risk of WMSDs to the type of work and the worker’s level of multifunctionality. For monofunctional workers, exposure to the higher risk was related to cycle time and the technical actions within their activities, whereas for multifunctional workers, it was related to the range of motion, use of gloves and precision needed in activities. For monofunctional workers, greater risks were associated with a short activity cycle, whereas for multifunctional workers, they were associated with complementary and organizational factors. Moreover, workers whose intracellular activities were less than 30% of the total appeared to be less exposed to the risk of WMSDs.